Marine Biodiversity of Eastern Tropical Pacific Coral Reefs - Cortés Núñez, Jorge (2017)
The eastern tropical Pacific (ETP) is an isolated oceanic region exposed to extreme oceanographic conditions, including low salinity, low pH, high temperatures during El Niño, and low temperatures during La Niña and seasonal upwelling. The coral reefs in this region have a relatively limited suite of species compared to other coral reef areas of the world, but much like more diverse reefs the species present interact in complex ways. Here we synthezise the knowledge of taxonomic groups of reef organisms from prokaryotes to vertebrates, including algae, sponges, cnidarians, annelids and other worms, molluscs, crustaceans, echinoderms and fishes. We also present summaries on the biodiversity of associated functional groups and habitats, including (a) reef zooplankton and cryptic fauna, and (b) soft benthic environments, rhodolith beds and mesophotic environments. Several factors that structure the biodiversity of ETP coral reefs are explored, including biological, physical and chemical controls. ETP coral reefs are relatively simple systems that can be used as models for studying biodiversity and interactions among species. We conclude this review by highlighting pressing research needs, from very basic inventories to more sophisticated studies of cryptic assemblages, and to investigations on the impacts of natural and anthropogenic effects on ETP coral reef biodiversity.